Implikasi Penerbitan Green Sukuk terhadap Pertumbuhan Ekonomi dan Kinerja Keuangan Syariah di Indonesia - Indra, Yetti Afrida (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study aims to analyze the effect of green sukuk issuance on economic growth and Islamic financial performance in Indonesia over the period 2018–2023. Specifically, it examines the effect of green sukuk on economic growth, the effect of green sukuk on Islamic financial performance, the indirect effect of green sukuk on Islamic financial performance through economic growth, and the mechanisms through which green sukuk influences both variables. The study employs a mixed-methods approach with a sequential explanatory design that combines quantitative and qualitative analyses to obtain a comprehensive and holistic picture. Secondary data are obtained from BPS, OJK, Bank Indonesia, and the DJPPR of the Ministry of Finance for the period 2018–2023, while primary data are collected through semi-structured interviews with five key informants. The research population consists of 15 Islamic financial institutions and government agencies related to green sukuk, with a quantitative sample of 10 institutions selected using stratified random sampling. Quantitative data are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), whereas qualitative data are analyzed using thematic analysis. The findings show that green sukuk issuance has a positive and significant effect on economic growth and Islamic financial performance. In addition, economic growth is proven to significantly mediate the effect of green sukuk on Islamic financial performance. These results confirm that green sukuk is an effective sharia-compliant financing instrument for promoting sustainable economic growth while simultaneously strengthening the performance of the Islamic financial sector in Indonesia